Drivers and Inhibitors Determining Government-Enabled Digital Platform Adoption for MSMEs in West Papua Province: PLS-SEM and IPMA Analysis - Husna, Asmaul; Dedi I. Inan; Ratna Juita; Muhamad Indra (TEMATIK, 2025)
Digital transformation plays a vital role in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in developing regions. A case in point is Rumahekraf in West Papua Province, which faces infrastructure challenges such as limited internet access, inadequate technological devices, and insufficient digital training for MSME actors. In addition to infrastructure challenges, external factors such as economic conditions, local culture, and the digital divide also influence the adoption rate of this platform. This study aims to investigate the factors that drive and hinder its adoption. By combining the Technology Acceptance Model (TAM), Technology Readiness Index (TRI), and Performance Importance Map Analysis (IPMA). Particularly, this study examines the role of optimism, innovativeness, discomfort, and insecurity in shaping behavioral intention (BI) that might lead to usage behavior (UB). With a total of 157 respondents, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), the results showed that perceived ease of use (PEOU) and perceived usefulness (PU) have a significant effect on BI (R2=56.3%), while BI influenced UB (R2=58%). Optimism affects PEOU but not PU, this can be explained by the nature of optimism, which tends to reinforce confidence in one's ability to master technology rather than directly evaluating the platform's perceived benefits. While Innovativeness positively affects both. The findings emphasize that in areas with limited infrastructure, such as West Papua, prioritizing easy-to-use design and useful features is key to effective platform adoption. This research provides insights for policymakers and developers to improve strategies in promoting digital platform adoption among MSMEs.